2013
DOI: 10.1590/s2179-975x2013005000003
|View full text |Cite
|
Sign up to set email alerts
|

A multimetric index based on fish fauna for the evaluation of the biotic integrity of streams at a mesohabitat scale

Abstract: Aim: In this study, we evaluated the ability of the Index of Biotic Integrity (IBI), based on fish fauna, to discriminate between reference streams and degraded streams at a mesohabitat scale. Methods: We sampled the ichthyofauna of 96 mesohabitats (runs, riffles and pools) with electrofishing gear in six streams (three reference and three degraded) of comparable volume, width, and depth. Twelve attributes were tested separately for different mesohabitat types. Results: Ten of the metrics tested were used to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“…species inhabiting only headwater streams; hereafter, Streams), large river specialists (Rivers), and ubiquitous Mean (±SD), minimal and maximal values are given for each variable species known to inhabit both small streams and large rivers (Ubiquitous) (Appendix S1). All sites were characterized by five regional (river basin membership), stream reach (stream width) and local (percentage of coarse substratum, litter and wood) environmental attributes that are known to be the main determinants of fish assemblage richness and composition (Jackson et al 2001;Bojsen and Barriga 2002;Wright and Flecker 2004;Casatti and Teresa 2012). The river membership (i.e.…”
Section: Sampling Methodologymentioning
confidence: 99%
“…species inhabiting only headwater streams; hereafter, Streams), large river specialists (Rivers), and ubiquitous Mean (±SD), minimal and maximal values are given for each variable species known to inhabit both small streams and large rivers (Ubiquitous) (Appendix S1). All sites were characterized by five regional (river basin membership), stream reach (stream width) and local (percentage of coarse substratum, litter and wood) environmental attributes that are known to be the main determinants of fish assemblage richness and composition (Jackson et al 2001;Bojsen and Barriga 2002;Wright and Flecker 2004;Casatti and Teresa 2012). The river membership (i.e.…”
Section: Sampling Methodologymentioning
confidence: 99%
“…For each RGB mosaic, we classified the key components of the riverscape, including fluvial mesohabitats (MHs), in-stream fluvial geomorphic features (GFs), and riparian cover (RC). MHs were classified into "run", "riffle", "pool", and "standing water" based on the appearance of the water surface structure to indicate flow velocity, depth visibility, and streambed substrate grain size [63][64][65]. We classified GFs into "gravel bar", "bedrock", and "dead wood".…”
Section: Supervised Classification Of Rgb Imagerymentioning
confidence: 99%
“…Riffles were shallow, with a rocky or gravelly substrate and a strong to moderate current. Pools had a greater depth, an unconsolidated (litter) or sandy substrate, and a slow stream flow (near zero), while runs had intermediate values of these parameters, i.e., a moderate depth and current and a sandy substrate (Casatti and Teresa 2012;Gosselin et al 2012). Additionally, 15 sites were grouped into three classes of increasing relative human impact:…”
Section: Selection Of Mesoscale Habitats and Land-use Patternmentioning
confidence: 99%
“…Although it has been reported that fish respond to different types of mesohabitats (Gelwick 1990;Langeani et al 2005;Kennard et al 2005), this information was not directly considered in the fish biotic indices previously proposed, and the IBI protocols were assessed over an entire stream rather than reach or specific site (covering about 200 m). Thus, ecological responses to the disturbance or chemical pollutions were irregular in a particular way in each mesohabitat type over or underestimating certain metrics if the stretch is considered as a whole (Casatti and Teresa 2012;Teresa and Casatti 2010).…”
Section: Introductionmentioning
confidence: 99%